2022
DOI: 10.3390/plants11050613
|View full text |Cite
|
Sign up to set email alerts
|

Plant Genotype Shapes the Bacterial Microbiome of Fruits, Leaves, and Soil in Olive Plants

Abstract: The plant microbiome plays an important role in plant biology, ecology, and evolution. While recent technological developments enabled the characterization of plant-associated microbiota, we still know little about the impact of different biotic and abiotic factors on the diversity and structures of these microbial communities. Here, we characterized the structure of bacterial microbiomes of fruits, leaves, and soil collected from two olive genotypes (Sinopolese and Ottobratica), testing the hypothesis that pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
(79 reference statements)
3
20
0
1
Order By: Relevance
“…According to previous research on wheat (Donn et al 2015;Azarbad et al 2020;Yergeau, Quiza, and Tremblay 2020) and other plant species (Wagner et al 2016;Brown et al 2020;F. Liu et al 2019;Malacrinò, Mosca, et al 2022), we hypothesize to detect a strong genotype-depend signal on the structure of fungal communities within each group.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…According to previous research on wheat (Donn et al 2015;Azarbad et al 2020;Yergeau, Quiza, and Tremblay 2020) and other plant species (Wagner et al 2016;Brown et al 2020;F. Liu et al 2019;Malacrinò, Mosca, et al 2022), we hypothesize to detect a strong genotype-depend signal on the structure of fungal communities within each group.…”
Section: Introductionmentioning
confidence: 62%
“…A genotype-driven effect on plant microbiome has been previously shown for several plant species (Wagner et al 2016;Brown et al 2020;F. Liu et al 2019;Malacrinò, Mosca, et al 2022;Wassermann et al 2022), but also among wheat varieties (Kavamura et al 2021). Indeed, previous research found that wheat genotype can shape the diversity and structure of microbial communities in bulk soil (Yergeau, Quiza, and Tremblay 2020), rhizosphere (Donn et al 2015;Mahoney, Yin, and Hulbert 2017;Azarbad et al 2020;Kavamura et al 2020;Rossmann et al 2020;Simonin et al 2020;Wolińska, Kuźniar, and Gałązka 2020), roots (Azarbad et al 2020;Cui et al 2022), and leaves (Azarbad et al 2020;Sapkota, Jørgensen, and Nicolaisen 2017;Žiarovská et al 2020).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Vita et al 10.3389/fpls.2022.992395 Frontiers in Plant Science frontiersin.org potentially related to growing conditions, where the presence of an inert substrate like perlite could have hampered the own plant's possibility to establish an efficient endophytic community. It is in fact possible to hypothize that using a natural soil, where microbial communities generally show an high biodiversity, the endophytic bacterial communities in leaves could reflect the complexity present in soil (Malacrinò et al, 2022). The bacterial communities inhabiting the leaves of all cultivars included members belonging to three main phyla, i.e., Proteobacteria, Actinobacteria and Firmicutes.…”
Section: B a Figurementioning
confidence: 99%
“…A comprehensive knowledge of microbial communities associated with the root system, including the root endosphere and the rhizospheric soil, has been recently reported by Fernańdez-Gonzaĺez et al (2019). Regarding the endophytic/epiphytic composition in the olive trees, recent studies have shown that differences emerge when different cultivars (Mina et al, 2020) and diverse European origin areas (Müller et al, 2015) are taken into account, or the microbiome profile of plant tissues is comparatively evaluated (Malacrinò et al, 2022). The microbiota of olive roots across different seasonal patterns was also elucidated (Chialva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%